2022
DOI: 10.21203/rs.3.rs-1948325/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

68Ga-Pentixafor PET/CT imaging for in-vivo CXCR4 receptor mapping in different lung cancer histologic sub-types: Correlation with quantitative receptors’ density by immunochemistry techniques

Abstract: Purpose In-vivo CXCR4 receptor quantification in different lung cancer (LC) sub-types using 68Ga-Pentixafor PET/CT and correlation with quantitative CXCR4-receptors’ tissue density by immunochemistry analyses. Methods 68Ga-Pentixafor PET/CT imaging was performed prospectively in 94 (77M: 17F, mean age 60.15 ± 10.12 yrs) LC patients. CXCR4 receptors’ expression was estimated in all the patients on lung tissue by immunohistochemistry (IHC) and FACS analyses. SUVmax on PET, Intensity score on IHC and Mean fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…A positive correlation was found between 68 Ga-pentixafor splenic uptake and platelet or leukocyte counts in lung cancer and neuroendocrine tumors, suggesting that splenic uptake might play a role in systemic immunity or inflammation (18). We previously reported that uptake of 68 Ga-pentixafor in SCLC patients was higher than in NCSLC and other lung cancer variants and that the uptake varied as a function of CXCR4 receptor density (11,14). However, the pattern of uptake and the in vivo evidence of CXCR4 expression in rare lung malignancies have not been studied before.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A positive correlation was found between 68 Ga-pentixafor splenic uptake and platelet or leukocyte counts in lung cancer and neuroendocrine tumors, suggesting that splenic uptake might play a role in systemic immunity or inflammation (18). We previously reported that uptake of 68 Ga-pentixafor in SCLC patients was higher than in NCSLC and other lung cancer variants and that the uptake varied as a function of CXCR4 receptor density (11,14). However, the pattern of uptake and the in vivo evidence of CXCR4 expression in rare lung malignancies have not been studied before.…”
Section: Discussionmentioning
confidence: 98%
“…According to the available literature, noninvasive imaging of CXCR4 expression in SCLC is feasible, and 68 Ga-pentixafor as a novel PET tracer might serve as a readout for confirming the CXCR4 expression (20). Watts et al reported that 68 Ga-pentixafor uptake denoting CXCR4 expression is higher in SCLC than NSCLC patients (11,14). Evaluation of CXCR4 expression is a prerequisite for potential CXCR4-directed radiotherapies and chemotherapies in lung cancer and especially in SCLC, which has higher CXCR4 expression compared with all other variants of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation